DISC1 knockdown impairs the tangential migration of cortical interneurons by affecting the actin cytoskeleton - Steinecke, André; Gampe, Christin; Nitzsche, Falk; Bolz, Jürgen (Frontiers in Cellular Neuroscience, 2014)
Disrupted-in-Schizophrenia 1 (DISC1) is a risk gene for a spectrum of major mental disorders. It has been shown to regulate radial migration as well as dendritic arborization during neurodevelopment and corticogenesis. In a previous study we demonstrated through in vitro experiments that DISC1 also controls the tangential migration of cortical interneurons originating from the medial ganglionic eminence (MGE). Here we first show that DISC1 is necessary for the proper tangential migration of cortical interneurons in the intact brain. Expression of EGFP under the Lhx6 promotor allowed us to analyze exclusively interneurons transfected in the MGE after in utero electroporation. After 3 days in utero, DISC1 deficient interneurons displayed prolonged leading processes and, compared to control, fewer neurons reached the cortex. Time-lapse video microscopy of cortical feeder-layers revealed a decreased migration velocity due to a reduction of soma translocations. Immunostainings indicated that DISC1 is co-localized with F-actin in the growth cone-like structure of the leading process. DISC1 knockdown reduced F-actin levels whereas the overall actin level was not altered. Moreover, DISC1 knockdown also decreased levels of phosphorylated Girdin, which cross-links F-actin, as well as the Girdin-activator pAkt. In contrast, using time-lapse video microscopy of fluorescence-tagged tubulin and EB3 in fibroblasts, we found no effects on microtubule polymerization when DISC1 was reduced. However, DISC1 affected the acteylation of microtubules in the leading processes of MGE-derived cortical interneurons. Together, our results provide a mechanism how DISC1 might contribute to interneuron migration thereby explaining the reduced number of specific classes of cortical interneurons in some DISC1 mouse models.